New Technology, Innovation and Space - Rossetos Fakiolas (European Regional Science Association (ERSA), 2006)
The new geography of the R&D activities As a rule, new technologies in today's world are the result of a long R&D process. This includes basic theoretical and applied research, as well as repeated testing which ensures that the new techniques coming out of the previous processes are ready to be applied in production and/or to enrich the output-mix with new products. In a broader sense, R&D generates also new ideas and techniques that contribute to the introduction of more efficient methods in the organization of production. In that part in which the non-marketable results are significant, the R&D activity is primarily state funded or financed by international organizations. It manifests a wide spatial distribution, spreading practically to all countries, and includes mainly research aiming to improve public health and security conditions, and to raise agricultural efficiency. It aims also to increase environmental protection and to create positive external economies that promote the public interest. In many big countries a considerable amount of state funded research serves military purposes and the exploration of space, with some of it having spillover effects for peaceful purposes. In the remaining part of the R&D that is conducted in the private sector of the economy, the Multinational Enterprises (MNEs) are the dominant players. In the era of globalization they have emerged as principal economic actors and are even more important in the application of new technologies. They dispose of large material resources and can recruit scientific and engineering talent from all over the world. It matters therefore where they locate their R&D. Given that the developed countries spend on R&D 2-3% of their GDP, amounting to the largest part of the world research expenditure, the traditional view has been that those countries account also for nearly all research activity. According to the UN World Investment Report 2005, however, the view of more complex production activities being undertaken in the North and simpler ones in the South is less and less a true reflection of reality. In some developing countries like China, India, Pakistan and North Korea, the state budget allocations for R&D expenses, including those for military research, has been high. The actual research output per unit of expense may be even higher, in comparison to that of the developed countries, because their wage levels and the cost of the basic infrastructure (building and various kinds of materials) are lower. Many of their researchers, however, are not less efficient and inventive than their homologues in the more developed countries. Further, MNEs now view parts of the developing world not only as key sources of cheap labour, but also of growth, skills and even new technologies. They have accelerated the pace of their direct investment in overseas R&D and the delocation of R&D activities in other countries, acquiring or establishing new laboratories abroad and integrating them into global R&D networks. They have many reasons to implement those policies: Their purpose is to source foreign technology, gain access to the local science base, hire foreign skilled engineers and benefit from local expertise and scientific excellence. They also want first, to utilize their subsidiaries in adapting the local market products to those developed in the research laboratories of the mother multinational company; and second, to adjust their own products to the local market and manufacturing processes. R&D activities of acquired subsidiaries are more concerned with applied research and scanning of local technologies, while new established subsidiaries generally focus on the suitable for the local market development of products based on technologies applied in the mother company. All told, small and less developed countries contribute now substantially to the world research output in three main ways: By running their own public and private research centers; as partners and employees of the subsidiaries of the MNEs established in them; and through their nationals doing research work in foreign universities and research centers. Despite its alleged detrimental effects, globalization, whatever its definition, appears to be reducing at a quick pace the spatial inequalities in research activities. The ways and means of those developments and their actual effects will be analyzed in the proposed paper. Policy implications Exploring the spatial allocation of the R&D activity may lead to useful conclusions for rational policy decisions. The establishment of MNEs in any country has overall positive labour market affects. It may, however, cause unemployment to the less qualified workers, in the usual cases that labour intensive processes are introduced in production lines carried out with traditional techniques. R&D activities established by the MNEs in a host country generate also positive spillovers in it, by strengthening its policies designed to attract FDI in research and innovation, as well as through an increase in the local demand for highly qualified persons. The more pronounced the presence of foreign R&D subsidiaries in a host country, the higher the demand for domestic researchers. It follows that well trained and with appropriate work attitudes graduates of tertiary education in any country can find satisfactory employment, at home or abroad. The national borders are also open for the highly skilled. Far from causing a brain drain, their emigration develops, as a rule, into a brain gain because it creates incentives for more and better training in the sending country. Eventually, it develops also into a brain exchange between sending and receiving countries, for their mutual benefit. In the last fifteen years, for example, the Chinese and Indian researchers in the universities and the technological parks of many developed countries have contributed considerably to the economic development of their respective countries. Up until very recently, in Greece as well about nine out of ten persons with responsible positions in the academia, the research centers and practically in all walks of life had some research experience abroad. The hypothesis which will also be tested in the proposed paper is that, higher degrees of R&D internalization are associated with minimal negative effects of any brain drain Main Bibliography Bein M. and Docquier Fr 2004 "Skilled Migration", Brussels Economic Review, Vol. 47-No1, Spring, Special Issue Cornelius W., EspenshadeT. J. and Salehyan I. 2001 "The International Migration of the Highly Skilled: Demand, Supply, and Development Consequences in Sending and Receiving Countries" La Jolla, Uni. of California, San Diego United Nations 2005 "World Investment Report 2005. Transnational Corporations and the Internationalization of R&D", New York and Geneva Various publications in English and Greek by Lambrianidis L., Liargovas P., Liberaki Ant., Petrakos G., Pournarakis M. and Thardanidis Ch.
Keywords: 330